Combination of cycle threshold time, absolute lymphocyte count and neutrophil:lymphocyte ratio is predictive of hypoxia in patients with SARS-CoV-2 infection. (11th December 2021) - Abeysuriya, Visula; Seneviratne, Suranjith L; de Silva, Arjuna P; Mowjood, Riaz; Mowjood, Shazli; de Silva, Thushara; de Mel, Primesh; de Mel, Chandima; Chandrasena, Lal; Wijesinha, R S; Fernando, Amitha; de Mel, Sanjay
Abstract: Background: There is currently no clinically validated biomarker to predict respiratory compromise in sudden acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Cycle threshold time (Ct), absolute lymphocyte count (AL) and neutrophil:lymphocyte ratio (NLR) have been previously evaluated for this purpose. We hypothesized that the combination of these parameters at presentation may be predictive of hypoxia (oxygen saturation <92%). Methods: Data were collected on 118 patients with SARS-CoV-2 infection between May 2020 and April 2021. Demographics, clinical parameters and laboratory and radiological investigation results were recorded. Respiratory compromise (RC) was defined based on symptoms and signs, hypoxia and chest X-ray abnormalities. Results: RC occurred in 61 (51.7%) of patients. The Ct, AL and NLR at median day 3 of illness were significantly different between patients with and without RC (Ct, RC vs not: 19.46±2.64 vs 22.62±3.37, p=0.0001; AL, RC vs not: 531.49±289.09 vs 764.69±481.79, p=0.0001; NLR, RC vs not: 3.42±0.75 vs 2.59±0.55, p=0.0001). Receiver operating characteristics analysis showed that a Ct <19.9, AL <630.8×10 3 /μL and NLR >3.12 at median day 3 of symptoms was predictive of hypoxia on day 7 of illness (area under the curve 0.805, sensitivity 96.7%, specificity 69.1%). The predictive value for the parameters combined was significantly superior to their individual predictive power. Conclusions: Ct, AL and NLR used in combination on day 3 of symptoms are predictive of hypoxia on day 7 of SARS-CoV-2 illness.